Topography of the inferior mandibular canal - Medina Lery M.
It is the purpose of this paper to study the course of the mandibular canal (inferior) and the neurovascular tissue in it, as it is one of the most important structure to consider in the clinical practice of oral surgery and to determine the location of the mental foramen in relation to the course of the inferior mandibular canal. The results show that only a very small minority of mandibular canals show any degree of high/low asymmetry. The infero-superior location of the mental foramen is not influences by variation in the intramandibular course of the inferior alveolar nerve.